Conservation behaviors of local communities towards mangrove forests in Iran - Moslem Savari; Hamed Eskandari Damaneh; Hadi Eskandari Damaneh (Global Ecology and Conservation)
Mangrove forests are a sensitive and fragile ecosystem at risk of extinction and destruction due to excessive exploitation in recent years. Moreover, insufficient studies, programs, and practical policies to safeguard these ecosystems have exacerbated their degradation. In this context, the present research was conducted to find the factors that determine the willingness of Iranian rural households towards mangrove forest conservation. The extended protection motivation theory (PMT) by adding the variables of moral norms (MN) and knowledge was used as the study's theoretical framework. This research was conducted using the questionnaire survey method and with the help of structural equations (SEM). The research's statistical population comprised all rural communities within Minab city in southern Iran. The findings of the research showed that the initial PMT explains 0.54 % of the variance of behavioral intention of rural households in applying forest conservation behaviors. The primary constructs of the PMT encompass perceived severity, perceived vulnerability, self-efficacy, response efficacy, and response costs, each of which positively influences the behavioral intention of rural households. Notably, the incorporation of knowledge and MN variables enhances the model's explanatory power regarding the BI of rural households to forest conservation by 21.8 %. In the current research, knowledge was identified as the most important factor, so policymakers can promote safe behavior in the natural environment by emphasizing it and providing the basis for sustainable forest development.